Моделювання механічної поведінки еластомірних матеріалів за допомогою штучної нейронної мережі - Погребняк, Сергій Віталійович; Водка, Олексій Олександрович (Національний лісотехнічний університет України, 2018)
У ХХІ ст. нейронні мережі широко використовують у різних сферах, зокрема в комп'ютерному моделюванні та механіці. Така популярність через те, що вони дають високу точність, швидко працюють та мають дуже широкий спектр налаштувань. Створено програмний продукт із використанням елементів штучного інтелекту для інтерполяції та апроксимації експериментальних даних. Програмне забезпечення повинно коректно працювати та давати результати з мінімальною похибкою. Інструментом розв'язання задачі було використання елементів штучного інтелекту, а точніше – нейронних мереж прямого поширення. Збудовано нейронну мережу прямого поширення. Її навчив вчитель із використанням методу зворотного розповсюдження похибки на основі навчаючої вибірки попередньо проведеного експерименту. Для тестування було побудовано декілька мереж різної структури, що отримували на вхід однаковий набір даних, якого не використовували під час навчання, але він був відомий з експерименту. Отже, було знайдено похибку мережі за кількістю виділеної енергії та середньоквадратичним відхиленням. Докладно описано тип мережі та її топологію. Метод навчання і підготовки навчаючої вибірки також описано математично. Внаслідок проведеної роботи збудовано та протестовано програмне забезпечення з використанням штучної нейронної мережі та визначено її похибку.

In the 21st century neural networks are widely used in various fields, including computer simulation and mechanics. This popularity is caused by the fact that they give high precision, work fast and have a very wide range of settings. The use of artificial neural networks is one of the most popular alternative methods of constructing a deformation curve. With the right choice of the network parameters you can achieve good results not only in the approximation of data but also in the interpolation. The purpose of the work is creating a software product using elements of artificial intelligence for interpolation and approximation of experimental data. The software should work correctly and yield results with minimal error. The solution tool of the problem was use of elements of artificial intelligence but rather neural networks of direct distribution. The neural network of direct distribution was built and trained in this work. It was trained by a teacher (a teacher using the method of reverse error propagation) based on a learning sample of a pre-experiment. For each of the learning types the similarities are being found. During the training with the teacher there is a correction of weight coefficients. After each iteration, the teacher compares the network response and the response that should have been received and adjusts it in order to reduce the difference between the response of the network and the response of the experiment (this mistake is called the learning error). Several networks of different structures were built for testing which received the same dataset that was not used during the training but was known from the experiment. Thus, the network error was found in the amount of allocated energy and the mean square deviation. The article describes in detail the type of network and its topology. The method of teaching and preparing a teaching sample is also described mathematically. As a result of the work, the software was constructed and tested using the artificial neural network and its error was determined. As a result of the experiments it was obtained that the network gives a fairly good results in a well-trained network. This network allows in the future interpolating intermediate results with high accuracy and easily receiving the amount of radiated energy. Neural networks are often used to predict the properties of materials (including composite) from a data set.
Modeling of mechanical behavior of elastomeric materials using an artificial neural network
Keywords: штучна нейрона мережа; комп'ютерне моделювання; штучний інтелект; апроксимація; інтерполяція; програмне забезпечення; artificial neural network; computer modeling; artificial intelligence; approximation; interpolation; software